Energy, development, and economic growth in Colombia (2013)
Purpose: The aim of this study is to describe the causal relationships between energy use, development, and productivity in Colombia. Design/Methodology/Approach: The study was conducted by application of several econometric techniques. The time-series methodology used in this is based on the Granger causality test, which has been found appropriate by using the cointegration technique. Findings: This study shows that economic growth and development drive total energy consumption. The results regarding the relationship among energy, poverty, and inequality indicate that increases in gross domestic product and energy supply per capita contribute to decrease poverty. The results also confirm that access to modern energy services helps to decrease poverty. Moreover, the improvements in energy efficiency and decreases in CO2 emissions have contributed to development and growth. Practical Implications: The results of this study showed the importance of the formulation and adoption of good policies and strategies that encourage sustainable energy use to improve growth and development, especially in developing countries. Originality/Value: This chapter provides an empirical approach for finding the causal relationship between development, productivity, and energy consumption in Colombia. The methodology and the results used in this study could be used for exploring the importance of energy in the productivity and economic development. © Springer-Verlag London 2013.